AB0955 TRANSITIONAL CARE: A SINGLE CENTER ITALIAN EXPERIENCE. (June 2019) - Crisafulli, Francesca; Cattalini, Marco; Ricci, Francesca; Maffeis, Giada; Franceschini, Franco; Tincani, Angela; Frassi, Micol
Abstract : Background: Transitional care from paediatrics to adults is an important step in the growth of the adolescent patients. One of the final goals is to guarantee the continuity of health care, increasing compliance in treatment and visits. Objectives: To describe disease features and adherence to the follow-up in rheumatic patients that were transferred from Paediatric Clinic to our adult department. Methods: From May 2016 to May 2018 the transition has been performed with a visit in presence of both specialists and 28 patients were evaluated. For juvenile Idiopathic Arthritis (JIA) we registered: category of arthritis, extra-articular involvement, treatment (during paediatric follow-up and at the time of the first evaluation) and disease activity (using JADAS10-CRP and DAS28-CRP; table 1 ). Finally, to assess the efficacy of this transition-model, we compared the rate of losses at follow-up with those occurred until 2016, when transition was performed only with a Clinical Report sent by paediatrician. Results: Between May 2016 and May 2018, 28 patients were enrolled (6 male, 22 female); mean age at diagnosis was 8.1 years (range 1-6 years); mean age at transition was 18.5 years (range 17-21 years). Twenty patients had a diagnosis of JIA, 3 of Undifferentiated Connective Tissue Disease, 1 Dermatomyositis, 1 Systemic Lupus Erythematosus, 1 Takayasu Arteritis, 1 Morphea, 1 Raynaud's phenomenon. Among JIA, 6 (30%) were Persistent Oligoarthritis, 4 (20%) Extended Oligoarthritis, 8 (40%) Polyarthritis (RF negative), 1 (5%) Psoriatic Arthritis, 1(5%) Enthesitis Related Arthritis. Five patients (25%) had history of uveitis. Treatment during the paediatric follow-up period are summarized in table 2 . At the time of first evaluation in adult department, 2 patients (10%) were on treatment with systemic steroids (5mg/day), 6 (30%) with methotrexate, 2 (10%) sulfasalazine, 1 (5%) with hydroxychloroquine, 1 (5%) leflunomide; 10 patients (50%) were on treatment with bDMARDs (6 adalimumab, 3 etanercept, 1 infliximab). Mean JADAS10-CRP was 3.8 (range 0-17, SD 5.8) as mean DAS28-CRP was 1.65 (range 0.96-3.44, SD 0.72). In 7 patients, disease activity assessed with JADAS10 was moderate-high as it resulted low-absent using DAS28-CRP. The rate of patients classified as having moderate-high activity was significantly different using the two index (35% using JADAS10 vs 5% using DAS28-CRP, pvalue 0.044). Until 2016, 6 of 44 (11%) patients were lost to follow-up while in the period between May 2016 and May 2018 no patients were lost (11% vs 0; pvalue 0.042) Conclusion: Disease activity seems to be underestimated using DAS28-CRP as compared with JADAS10-CRP. This could be due to the more frequent involvement of ankles and feet (that are not included in DAS28-CRP) in JIA. The adherence to follow up was greater in patients whose transition was performed in presence of the two Specialists. Disclosure of Interests: Francesca Crisafulli: None declared, Marco Cattalini: None declared, Francesca Ricci: None declared, Giada Maffeis: None declared, Franco Franceschini: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Micol Frassi: None declared